2020
DOI: 10.1371/journal.pone.0237984
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density in HIV-positive young Italians and migrants

Abstract: Background Human immunodeficiency virus (HIV) infected individuals may have osteoporosis. We aimed to evaluate the bone mineral density (BMD) in naïve antiretroviral (ARV) treated HIV positive patients comparing native Italian group (ItG) to a Migrants group (MiG) upon arrival in Italy. Methods We conducted a cross-sectional study on 83 HIV patients less than 50 years old. We used the dual-energy X-ray absorptiometry (DXA) within six months from the HIV diagnosis. Participants were categorized as having low BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Brown et al 19 found the rate of decreased BMD in an ART-naive group of patients younger than 50 years old as 10%, while Paccou et al 20 found the same rate as 24.5% in a similar group. Cascio et al 21 compared Italian patients younger than 50 years old and lived with HIV and migrant patients based on their Z-scores and found their rates of low BMD as 13.6% and 37.5%, respectively. These researchers reported that the lumbar region was affected the most, a result similar to what was found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al 19 found the rate of decreased BMD in an ART-naive group of patients younger than 50 years old as 10%, while Paccou et al 20 found the same rate as 24.5% in a similar group. Cascio et al 21 compared Italian patients younger than 50 years old and lived with HIV and migrant patients based on their Z-scores and found their rates of low BMD as 13.6% and 37.5%, respectively. These researchers reported that the lumbar region was affected the most, a result similar to what was found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vitamin D may have a crucial role in bone osteoporosis, which may be essential in migrants and individuals with HIV infection [39][40][41][42][43]. Child neglect cases discovered in forensic practice and unpublished cases debated only in courts may represent the tip of an iceberg [29,44].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Thymus depletion is a usual finding in human-immunodeficiency virus (HIV) infected patients, but a refurbishment of the thymus function in children has been proposed in some virologic responders treated with multidrug combinations of antiretroviral agents ( 1 3 ). In addition, studies from children with acquired immunodeficiency syndrome (AIDS) have clarified the pathogenesis of some primary tissue lesions ( 2 , 4 , 5 ).…”
mentioning
confidence: 99%